Vasodilatator Beta Blockers in Cardiovascular Disease - (:unkn) unknown (AVES YAYINCILIK, IBRAHIM KARA, 2010)
Beta adrenergic agonists (beta-blockers) have proven effects in cardiovascular area. However, their usage as first-line treatment had started to be questioned recently due to their side effects, mainly systemic hypertension. Therefore, third generation agents with less side effects and more beta 1 selectivity have started to be used in clinical cardiology in the last decades. Although these agents were targeted to be used for the treatment of chronic heart failure at the begining, they have started to be used as the first-line treatment for some other indications, mainly for hypertension, as they have a good efficacy and tolerability profile and have less metabolic side effects. In this article, vasodilatator beta-blockers were reviewed in detail with the guidance of clinical trials performed in this area.
Keywords: beta-blocker; vasodilatator; CHRONIC HEART-FAILURE; LEFT-VENTRICULAR DYSFUNCTION; ACUTE MYOCARDIAL-INFARCTION; RANDOMIZED-TRIAL; METOPROLOL CR; MERIT-HF; CARVEDILOL; MORTALITY; OPTIMIZATION; BUCINDOLOL